Quantification of Local Electric Field Changes at the Active Site of Cytochrome c Oxidase by Fourier Transform Infrared Spectroelectrochemical Titrations - Baserga, Federico; Dragelj, Jovan; Kozuch, Jacek; Mohrmann, Hendrik; Knapp, Ernst-Walter; Stripp, Sven T.; Heberle, Joachim (Frontiers in Chemistry, 2021)
Cytochrome c oxidase (CcO) is a transmembrane protein complex that reduces molecular oxygen to water while translocating protons across the mitochondrial membrane. Changes in the redox states of its cofactors trigger both O2 reduction and vectorial proton transfer, which includes a proton loading site yet unidentified. In this work, we exploited carbon monoxide as a vibrational Stark effect probe at the binuclear center of CcO from R. sphaeroides. The CO stretching frequency was monitored as a function of the electrical potential using Fourier transform infrared (FTIR) absorption spectroelectrochemistry. We observed three different redox states (R4CO, R2CO, O), determined their midpoint potentials, and compared the resulting electric field to electrostatic calculations. A change in the local electric field strength of +2.9 MV/cm was derived, which was induced by the redox transition from R4CO to R2CO. We performed potential-jump experiments to accumulate the R2CO and R4CO species and studied the FTIR difference spectra in the protein fingerprint region. The comparison of experimental and computational result reveals that the key glutamic acid residue E286 is protonated in the observed states and that its hydrogen-bonding environment is disturbed upon the redox transition of heme a3. Our experiments also suggest propionate A of heme a3 changing protonation state in concert with the redox state of a second cofactor, heme a. This supports the role of propionic acid side chains as part of the proton loading site.